ENHANCING LEARNING EFFECTIVENESS STRATEGY: SELF-DIRECTED LEARNING AND LEARNING FACILITIES AT SMK TEKNIK PAL SURABAYA - Imanuddin, Faiq; Darmawan, Didit (JURNAL AL-QAYYIMAH, 2023)
Learning effectiveness is the main key in achieving learning goals. With the aim of knowing the extent to which students can understand and apply the subject matter being taught. Therefore, this study aims to investigate how learning independence and learning facilities contribute to the effectiveness of student learning. The population of this study is aimed at students of the PAL Surabaya Engineering Vocational School. Quality education is the main key to forming educated and qualified human resources. Factors such as student learning independence and available learning facilities are considered to play an important role in increasing learning effectiveness. Learning methods are considered effective if they are able to achieve instructional goals optimally. This study uses a quantitative approach using survey methods and regression analysis. The study sample involved 75 students from class XII majoring in Computer Networks at PAL Engineering Vocational School, Surabaya. The study results show that learning independence and learning facilities significantly influence student learning effectiveness. The implications of these findings provide a basis for improving learning strategies and learning facilities to improve the quality of education at the PAL Technical Vocational School, Surabaya.